2003
DOI: 10.1159/000068478
|View full text |Cite
|
Sign up to set email alerts
|

Cerebrospinal Fluid Beta-Amyloid 42 Is Reduced before the Onset of Sporadic Dementia: A Population-Based Study in 85-Year-Olds

Abstract: Deposition of β-amyloid (Aβ) is an early pathogenic event in Alzheimer’s disease (AD). We measured Aβ42 and Aβ40 in cerebrospinal fluid (CSF) in a population-based sample of 85-year-olds, 27 demented and 35 non-demented. During the following 3 years, 7 of the 35 non-demented individuals had developed dementia, while 28 remained non-demented. Reduced CSF levels of both Aβ42 (p = 0.001) and Aβ40 (p = 0.0001) were found in patients with manifest AD and vascular dementia at the age of 85. Non-demented individuals … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
106
0
1

Year Published

2004
2004
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 176 publications
(113 citation statements)
references
References 39 publications
6
106
0
1
Order By: Relevance
“…Aβ accumulation and deposition in the AD brain can begin 10 y before the appearance of the first symptoms (2, 32). The concept of "preclinical AD" indicates that AD pathologies are present but AD symptoms are not (49,50). Several anti-Aβ therapeutic strategies are being pursued to treat AD; however, it is likely that treatment will need to begin during the preclinical phase to prevent or limit plaque accumulation to be beneficial in reducing the risk of developing AD (51,52).…”
Section: Discussionmentioning
confidence: 99%
“…Aβ accumulation and deposition in the AD brain can begin 10 y before the appearance of the first symptoms (2, 32). The concept of "preclinical AD" indicates that AD pathologies are present but AD symptoms are not (49,50). Several anti-Aβ therapeutic strategies are being pursued to treat AD; however, it is likely that treatment will need to begin during the preclinical phase to prevent or limit plaque accumulation to be beneficial in reducing the risk of developing AD (51,52).…”
Section: Discussionmentioning
confidence: 99%
“…112 A recent population-based study also found that reduced CSF A␤42 is present in asymptomatic elderly who developed dementia during a 3-year follow-up period. 113 The fact that only ϳ15% of MCI cases progress to AD each year 6 makes a very extensive follow-up period (more than 5 years) needed to ascertain which MCI patients will not develop dementia, i.e., have stable MCI. This may introduce a risk that the specificity figures in these studies thus far are too low.…”
Section: MCImentioning
confidence: 99%
“…Two population-based studies have found a significant reduction in CSF Aβ42 in cognitively normal elderly people that later developed dementia [11,12]. In the same material, there was no significant change in CSF T-τ or P-τ in individuals that later developed AD 'CSF biomarkers, especially CSF Aβ42, may predict preclinical AD in cognitively normal elderly individuals.…”
Section: Csf Biomarkers To Identify Ad Preclinicallymentioning
confidence: 93%